Principles of nasal reconstruction - Baker, Shan R. (Springer, 2011)
Principles of Nasal Reconstruction, Second Edition, is a comprehensive, in-depth resource written by one of the world’s foremost practitioners of nasal reconstruction. This thoroughly revised and updated textbook discusses a wide range of basic and advanced nasal reconstructive procedures in patients presenting with a variety of partial and full thickness defects of the nose. Part One discusses the fundamentals of nasal reconstruction. It provides algorithms to assist the surgeon in selecting the preferred method of restoring internal lining, structural support, and external cover, all of which are governed by the extent of the nasal defect and availability of resources that can be used for the repair. Part Two represents the “how to” section of the book. It provides detailed step-by step discussions of techniques used to design, dissect, transfer and refine flaps and grafts used in nasal reconstruction. It also reviews the prevention and management of complications. In Part Three, each chapter discusses a representative case or cases that demonstrate typical complications and limitations confronting all surgeons when reconstructing the nose. Designed so practitioners can add to their surgical repertoire with a thorough reading, or quickly consult the text aided by detailed labeling and hundreds of photographs, Principles of Nasal Reconstruction is an invaluable resource for otolaryngologists, head-and-neck surgeons, and plastic and reconstructive facial surgeons. About the Author Shan R. Baker, M.D., is Professor and Chief of the section of Facial Plastic and Reconstructive Surgery and Director of the Center for Facial Cosmetic Surgery in the Department of Otolaryngology Head and Neck Surgery, University of Michigan Health System. He has more than 30 years of surgical experience in reconstructing the nose. History of nasal reconstruction -- Anatomic considerations -- Preparation of the patient -- Internal lining -- Structural support -- External covering -- Cartilage grafts -- Bone grafts -- Skin and composite grafts -- Nasal cutaneous flaps -- Intranasal flaps -- Subcutaneous tissue pedicle hinge cheek flaps -- Interpolated melolabial flaps: reconstruction of alar and columellar units -- Interpolated paramedian forehead flaps -- Refinement techniques -- Complications and management -- Reconstruction of lateral tip: two methods of repair -- Reconstruction of central tip: three methods of repair -- Reconstruction of tip, dorsum, sidewalls, and ala -- Sequential interpolated paramedian forehead flaps -- Reconstruction of tip, ala, and caudal sidewall: two concurrent defects -- Two methods of repair -- Reconstruction of nasal facet, ala, and caudal sidewall: three consecutive defects -- Reconstruction of lateral tip and ala -- Bilateral interpolated paramedian forehead Flaps -- Reconstruction of nasal sidewall and dorsum -- Reconstruction of ala, cheek, and upper lip -- Reconstruction of hemi-tip and ala with single interpolated paramedian forehead flap for lining and cover -- Reconstruction of tip, columella, and ala -- Near-total nasal reconstruction -- Reconstruction of nasal dorsum, sidewall, cheek, and medial orbit.